Lifestyle of medical students: Življenjski slog študentov medicine - Žnidarič, Matej; Zavodnik, Iza; Lučič Šrajer, Lucijan (Acta Medico-Biotechnica, 2021)
Purpose: Using the World Health Organization definition that a healthy lifestyle is a way of living that lowers the risk of serious illness or early death, our goal was to examine the lifestyle changes made by medical students over the years of study. A healthy lifestyle, which is crucial to maintain and protect health, is determined by many variables, both positive and negative.Methods: A total of first, third and fifth year medical students at the Faculty of Medicine of the University of Maribor (165 students, 57 males and 108 females) were enrolled in the study during the academic year 2017/18. Lifestyle data, including physical activity, nutrition, sleep hygiene, and drug, tobacco and alcohol use, were collected using a standardized self-assessment questionnaire, the FANTASTIC Lifestyle Assessment Instrument, which had been translated into Slovenian. The questionnaire was supplemented with further questions to explore psychological aspects of lifestyle, such as mental well-being, social inclusion, altruism and student activities.Results: Our sample of first, third and fifth year medical students revealed unhealthy changes in life habits, which were closely associated with the length of training. For the third year students, the situation had reached a crisis point, probably because the initial enthusiasm over choice of study had worn off, and stress had become less managable in the transition period between preclinical and clinical training. During their third year, the students consumed the largest amount of controlled substances and prescription and OTC drugs (p=0.003), lacked goals and purpose in life, were less connected with the faculty (p=0.000) and showed a decline in altruism (p=0.007).Conclusions: Our results show that the psychophysical stress burden among medical students increases with duration of training, reaching crisis point during the third year. We recommend that medical students should arrange self-help and support groups to maintain a healthier lifestyle during this challenging period.
Keywords: lifestyle; medical students; crisis; psychophysical strain